Optimization of BUMDes Dharma Abadi Human Resources in Apuan Village, Susut District, Bangli Regency - Ni Made Puspitasari Ujianti; Ida Ayu Putu Widianti; Dewa Agung Putu Purnama; I Wayan Sunarta; Putu Sandiawan Putra Wiranata; Ni Putu Laksmi Krisnina Maharani (Law Doctoral Community Service Journal, 2023)
Apuan Village is one of the villages in Susut District, Bangli Regency, which has a lot of tourism potential and water resource potential. Each village may have a Business Entity to manage village potential through its business units. So Apuan Village established the Dharma Yuda Abadi Village Unit Business Entity since 2017. The business units managed by BUMDes Dharma Yuda Abadi are savings and loan business units, management of drinking water supply and management of tourist objects. However, due to the lack of human resource management capabilities owned by BUMDes Dharma Yuda Abadi, the development of BUMDes which was expected to be able to improve community welfare and also be able to increase PADes in Apuan Village could not be achieved. One indicator of the lack of management capability of the Dharma Yuda Abadi BUMDes Human Resources is the rejection of the responsibility of the Dharma Yuda Abadi BUMDes manager for the 2020 fiscal year, of course this will affect the performance of the BUMDes in subsequent years.